Le paysage humanisé au Québec - Gérald Domon (Projets de Paysage)
In response to increasing social pressure, the government of Quebec created the status of the humanised landscape. As part of the law on the conservation of the natural heritage and of category V as defined by the International Union for the Conservation of Nature (IUCN), this status is intended for the protection and enhancement of certain areas “[...] constituted to protect the biodiversity of an inhabited territory, [...] the landscape and natural components which have been shaped by human activity in harmony with nature [...]”. By defining biodiversity as the starting point for acknowledging the importance of the landscape, the Quebec government adopted an original approach. However, 12 years later, no humanised landscape has been created. How can this difficulty for the status to find its practical role be explained? To what extent can the predominance given to biodiversity and therefore to the natural dimension of the landscape be explained? After describing the main aspects of the status, the article presents the research and studies which inspired the governmental approach to the landscape and led to the renewed division between nature and culture. On these bases, it proposes an analysis to understand the main factors this status has to contend with. The analysis reveals the limitations of sector-type approaches which, in the present case, led to reducing the scope of the landscape to that of natural ecology. By revealing the limits of such approaches, this status could become an experimental field for modernising the structures regulating the development of the region of Quebec.